2021
DOI: 10.15586/qas.v13i1.817
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fat meat and storage temperature on the qualities of frozen minced beef products

Abstract: The purpose of this study was to identify the ideal storage period for frozen minced beef products and to under-stand key factors affecting their quality. Frozen minced beef products with 10 and 15% of fat content were kept at ?5, ?15, and ?23°C, and over a 6-month period, they were assessed for moisture content (MC), peroxide values (POV), acid values (AV), 2-thiobarbituric acid (TBA) value, total volatile basic nitrogen content (TVB-N), and the sensory test in order to identify the effect on quality. This he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Then, regardless of fat content, the values dropped. [37],studied The impact of the best frozen minced beef products were identified, and two types were obtained from a local provider. The patties were manufactured with 10 and 15% fat content were kept at−5, −15, and −23°C, and peroxide levels (POV) were measured during a 6-month period, When storage began, POV of the 10% samples was 2.16 meq/kg, whereas for 15% samples, it was 2.49 meq/kg.…”
Section: The Third Stage: Terminationmentioning
confidence: 99%
“…Then, regardless of fat content, the values dropped. [37],studied The impact of the best frozen minced beef products were identified, and two types were obtained from a local provider. The patties were manufactured with 10 and 15% fat content were kept at−5, −15, and −23°C, and peroxide levels (POV) were measured during a 6-month period, When storage began, POV of the 10% samples was 2.16 meq/kg, whereas for 15% samples, it was 2.49 meq/kg.…”
Section: The Third Stage: Terminationmentioning
confidence: 99%
“…The oxidation of oils and fats is one of the greatest challenges that can lead to food spoilage and generate unpleasant smells, tastes, and inappropriate colors while reducing the nutritional value and undermining consumption safety (Azizi et al, 2021 ; Chailangka et al, 2023 ; Lee et al, 2021 ; Ugarte‐Espinoza et al, 2021 ). Oxidation products, such as hydroperoxides, hydroxyl radicals, and monovalent oxygen are harmful to human health and cause damage to biological cells (Amiri et al, 2021 ; Choudhary et al, 2023 ; Gonzalles et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [ 11 ] asserted that lower freezing temperatures could effectively reduce the denaturation of beef protein. Moreover, Lee et al [ 12 ] reported that the shelf life of frozen beef products gradually decreased as the frozen temperature increased (−5 °C, −15 °C, and −23 °C). Due to the special quality of snowflake beef, studying the impact of using different freezing temperatures on the storage of snowflake beef could provide a theoretical basis for efficient maintenance of imported snowflake beef quality.…”
Section: Introductionmentioning
confidence: 99%